A novel CRTH2 antagonist: Single‐ and multiple‐dose tolerability, pharmacokinetics, and pharmacodynamics of ACT‐453859 in healthy subjects. (30th March 2015) - Géhin, Martine; Strasser, Daniel S.; Zisowsky, Jochen; Farine, Hervé; Groenen, Peter M.A.; Dingemanse, Jasper; Sidharta, Patricia N.
Abstract The chemoattractant receptor‐homologous molecule expressed on T‐helper 2 cells (CRTH2) is a G‐protein‐coupled receptor for prostaglandin D2, a key mediator in inflammatory disorders. In this randomized, double‐blind, placebo‐controlled study we investigated the single‐ and multiple‐dose tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) up to a dose of 800 mg once a day of ACT‐453859, a potent and selective CRTH2 antagonist. ACT‐453859 was moderately rapidly absorbed and followed a biphasic elimination pattern, with an elimination half‐life between 11 and 20 hours. Steady‐state conditions were reached after 1 day, and ACT‐453859 did not accumulate. Urinary excretion of unchanged ACT‐453859 did not exceed 1.4% of the administered dose. Administration of ACT‐453859 resulted in a dose‐dependent blockadeof CRTH2 on the surface of eosinophils. The maximum PD effect of ACT‐453859 was reached about 2.0 hours after dosing, which corresponded to the highest concentration at which PD were assessed. At steady state, 100 and 800 mg ACT‐453859 once a day resulted in blockade of CRTH2 over 24 hours. In this entry‐into‐humans study, ACT‐453859 showed good tolerability at all doses and a PK and PD profile compatible with once‐daily dosing.